Tra ambizione e carriera. La professione di advocatus nello Stato della Chiesa tra XVI e XVIII secolo - Maria Macchi (Criminocorpus)
What do we know about roman lawyers life and careers in Ancient Regime? Which were theirs social strategies in and out of professional groups and institutions? How did many lawyers spend their time in Rome? In this essay I would like to explain several results of my research about lawyers in Rome and Church State between XIV and XVIII centuries. It is possible not only to study singular professional biography but also to reconstruct social- climbing instruments used by young lawyers to introduce themselves in the Papal court. Indeed a lot of men in Ancien Regime decided to invest time, studies and money in this profession with a very important objective: to be a member of “Avvocati Concistoriali” one of most representative professional group in Rome in modern history. It was not so easy to do it: candidates had to do a complex and long process to pass their admission exam and receive their formal clothes. In this essay I also analyse the prerogative of roman lawyers : the choice of family tomb, the urban residence, the family library. There is also a summary table about lawyers who decided to live in Rome to improve their careers and others who prefer spend just few years in Rome and then return in their native cities where they could obtain many important offices.